Perancangan Interior One Stop Klinik Anak di Surabaya - Tiffani Anggia Natasya; Sriti Mayang Sari (Intra, 2018)
Children are the future of the nation that need to get special attention during their period of growth and development. During the Golden Age phase, children will grow and develop quickly, when followed with excellent health quality. One Stop Children clinic is a facility that accommodate parents to know the development of children's health, educate children with educational games, and also educate the parents about children's health through seminars and workshops. Inside the children clinic, there is also a pharmacy that will provide a wide range of medicines for children, and cafes that served healthy foods and drinks. Thus, this one stop children clinic will provide a different service concept than the usual and general children clinic.